HUBUNGAN PENGETAHUAN DAN SELF EFFICACY PASIEN TB PARU DENGAN PENCEGAHAN PENULARAN TB PARU DI PUSKESMAS KOTA BUKITTINGGI - 1006038402 Lisa Fradisa (Universitas Pahlawan Tuanku Tambusai, 2022)
ABSTRACT Tuberculosis (TB) is an infectious disease that attacks the lungs caused by the bacteria Mycrobacterium Tuberculosis. Indonesia is the country with the second most TB patients in the world. Based on the data (Dinkes) of Bukittinggi City, it is obtained that in 2017 there were 71 pulmonary TB cases during the year in Bukittinggi City. While in 2018 cases of pulmonary TB increased to 90 people. From several statements of patients with pulmonary TB at Bukittinggi Public Health Center, it is known that respondents do not know how to prevent transmission to the family so there is no difference in eating utensils in the family. The purpose of this study was to determine the relationship of knowledge and Self Efficacy of Pulmonary TB patients with prevention of pulmonary TB transmission in the Work Area of ​​the Bukittinggi City Health Center. This research method uses descriptive analytic method with cross-sectional approach. The population was 39 patients who were diagnosed with pulmonary TB in the working area of ​​the Bukittinggi Puskesmas in total sampling. The results showed that most (82.1%) of respondents had sufficient knowledge, (53.8%) of respondents had high Self Efficacy, and (69.2%) of respondents had good TB prevention behaviors. The results of the bivariate analysis of the relationship of knowledge with the prevention of transmission p value = 0.002 and the relationship of Self Efficacy with the prevention of transmission p value = 0.035. In this study it can be concluded that there is a significant relationship between Knowledge and Self Efficacy of Lung TB Patients with Prevention of Lung TB Transmission. Suggestions in this study can be used as input for public health centers in Bukittinggi to be more active in efforts to promote health about tuberculosis by conducting socialization on prevention of pulmonary TB transmission. Key Word: Knowledge, Self Efficacy, Prevention of Lung TB Transmission